(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The finding of graffiti in ancient contexts such as Mas Gusó is not frequent. Mas Gusó is an autochthonous settlement with a long his- tory, closely related to Emporion for geographical as well as cultural rea- sons. The complexity of the archaeological field and the information it gives about a vast period is too rich to present it in a brief paper. Because of the interest of this graffito written in Greek characters and dated in the late sec- ond half or end of the 4th century, we have considered it worth to provide an especific study of the piece so that the scientific community may know it be- fore the monographical research of the whole field is published, a task that will have to wait until the end of the excavations and the acomplishment of a study that will last some years yet.